Dynamic Response of Green Sandwich Structures. (2016) - Sarasini, F.; Tirillò, J.; Lampani, L.; Valente, T.; Gaudenzi, P.; Scarponi, C.
Abstract: Synthetic fibre-synthetic foam core sandwich composites are widely used for many structural applications due to their superior mechanical performance and low weight but the limited end of life disposal options and environmentally friendly character are currently envisaged as barriers to their continued development. The objective of this article is to analyse the suitability of using agglomerated cork as core material in sandwich structures to be used in applications where energy absorption due to low velocity impacts can be of importance. Green sandwich specimens with flax/epoxy face sheets and agglomerated cork as core have been manufactured and their response to low velocity impacts has been compared to the results obtained with similar specimens using traditional synthetic core. This study shows that the peculiar deformation mechanisms of cork can allow to tailor the damage extension through-the-thickness thus providing in principle a better damage tolerance after impact.